Home management of malaria among caregivers of under-five children in Owo, Ondo State, Nigeria - Liasu Adeagbo Ahmed; Olubankole Akinboboye; Olayinka Stephen Ilesanmi; David Akintayo Oguntuase (Journal of Health and Social Sciences)
Introduction: Home management of fever by caregivers is particularly relevant for ensuring effective care to under-five children in Sub-Saharan countries with high-transmission of malaria like Nigeria. Our study aimed to assess home management of fever among mothers and other caregivers of underfive children attending Federal Medical Centre in Owo, Ondo State, Nigeria. Methods: A descriptive, cross-sectional hospital-based study was carried out. A systematic random sampling technique was used to recruit participants (mothers and other caregivers). A structured interviewer administered questionnaire was used. Clinical findings and malaria test were performed on children using standard methods. Data were analyzed with SPSS version 15. Results: Prevalence of home treatment of fever was 98.4%. Most of the caregivers bought antifever drugs from patent medicine shops and only 11.9 % of them got a prescription drug from pharmacies. Despite good knowledge about causes of malaria by caregivers (72.6%) and a prompt medical treatment within 24 h of fever onset (84.2%), many of their children were treated with only paracetamol (45%) and, therefore, they presented to the hospital febrile (61.8%), tachycardic (63.7%), and tachypnoic (83.9%). Almost all of the children were diagnosed with malaria (98%) associated with some types of complication such as convulsion (29.6%) and anaemia (52.7%). Chi square test showed a significant (P < 0.005) difference between treatment modality (inpatient versus outpatient) with regards to educational level, type of caregivers, place of domicile, use of antimalarial in combination with paracetamol, and presence of complications. Discussion and Conclusion: In our study, home management of malaria by caregivers of under-five children was ineffective. Indeed, the effectiveness of home management of malaria depends not only on the early diagnosis, but also on a prompt and appropriate treatment. Therefore, proper health education programmes on this disease should be implemented among caregivers of under-five children.